Upconverting Er3+, Yb3+ activated β-NaYF4 thin films: a solution route using a novel sodium β-diketonate polyether adduct. (25th May 2017) - Catalano, Maria R.; Pellegrino, Anna L.; Rossi, Patrizia; Paoli, Paola; Cortelletti, Paolo; Pedroni, Marco; Speghini, Adolfo; Malandrino, Graziella
Abstract : A new Na(hfa)·tetraglyme adduct has been synthesized and successfully applied, together with the RE(hfa)3 ·diglyme (RE = Y, Yb, Er) complexes, in the sol–gel synthesis of upconverting hexagonal NaYF4 :Yb 3+, Er 3+ films. Abstract : A new tetraglyme adduct of sodium hexafluoroacetylacetonate [Na(hfa)·tetraglyme] has been synthesized and successfully used, together with the RE(hfa)3 ·diglyme (RE = Y, Yb, Er) complexes, in the synthesis of hexagonal phase NaYF4 :Yb 3+, Er 3+ upconverting films through a facile sol–gel method.